Savanna Tree Seedlings are Physiologically Tolerant to Nighttime Freeze Events - O’Keefe, Kimberly (Front Plant Sci, 2016)
Freeze events can be important disturbances in savanna ecosystems, yet the interactive effect of freezing with other environmental drivers on plant functioning is unknown. Here, we investigated physiological responses of South African tree seedlings to interactions of water availability and freezing temperatures. We grew widely distributed South African tree species (Colophospermum mopane, Combretum apiculatum, Acacia nigrescens, and Cassia abbreviata) under well-watered and water-limited conditions and exposed individuals to nighttime freeze events. Of the four species studied here, C. mopane was the most tolerant of lower water availability. However, all species were similarly tolerant to nighttime freezing and recovered within one week following the last freezing event. We also show that water limitation somewhat increased freezing tolerance in one of the species (C. mopane). Therefore, water limitation, but not freezing temperatures, may restrict the distribution of these species, although the interactions of these stressors may have species-specific impacts on plant physiology. Ultimately, we show that unique physiologies can exist among dominant species within communities and that combined stresses may play a currently unidentified role in driving the function of certain species within southern Africa.